PERAN KEHARMONISAN KELUARGA DAN PENERIMAAN TEMAN SEBAYA TERHADAP KONSEP DIRI REMAJA SMP DI DENPASAR - Dewi, A.A. Ayu Trisna; Rustika, I Made (Jurnal Psikologi Udayana, 2014)
The self-concept is a very important mental aspect in a early adolescent’s life because it can influence their behavior. Self-concept is not innate, but rather influenced by environmental stimuli at an early age. Family condition is one of the environmental stimuli that can influence self-concept. In outside-the home life, the responses of peers while interacting also contribute significantly to the self-concept. This study aims to determine the roles of family harmony and peer acceptance to teenagers’ self-concept of Junior High School adolescent in Denpasar. Subjects in this study were 224 of Junior High School adolescent in Denpasar, represented by the State Junior High School 1 of Denpasar. Instruments in this study were self-concept scale, family harmony and scale of peer acceptance. The results of multiple regression analysis shows that R = 0.560 (F = 50.395, p <0.05), it can be stated that the harmony of the family and peer acceptance jointly contribute to the self-concept. Determination coefficient of 0.313 indicates that the effective contribution of family harmony and peer acceptance to the self-concept amounted to 31.3%. Standardized beta values on family harmony with the self-concept is 0.285 (p <0.05) whereas peer acceptance with the self-concept at 0.361 (p <0.05). Thus it can be stated the role of peer acceptance is greater than the harmony of the family for the self- concept.   Keywords: self-concept, family harmony, peer acceptance, junior high school adolescent